2010
DOI: 10.3390/ph3103040
|View full text |Cite
|
Sign up to set email alerts
|

Future Trends in the Pharmacogenomics of Brain Disorders and Dementia: Influence of APOE and CYP2D6 Variants

Abstract: About 80% of functional genes in the human genome are expressed in the brain and over 1,200 different genes have been associated with the pathogenesis of CNS disorders and dementia. Pharmacogenetic studies of psychotropic drug response have focused on determining the relationship between variations in specific candidate genes and the positive and adverse effects of drug treatment. Approximately, 18% of neuroleptics are substrates of CYP1A2 enzymes, 40% of CYP2D6, and 23% of CYP3A4; 24% of antidepressants are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 207 publications
(465 reference statements)
3
82
0
Order By: Relevance
“…The present results appear to indicate that the combination therapy used in this study, probably together with the lipid-lowering effects and anti-atherosclerotic properties of sardilipin [18,24,73] and the prometabolic activity of animon complex, exert a positive synergistic effect on brain function accompanied by a transient improvement in mental performance, lasting for about 9-12 months Figure 2. The effect of CDP-choline, either alone or in combination with donepezil, as well as the effects of sardilipin, are APOE-dependent [3,[18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…The present results appear to indicate that the combination therapy used in this study, probably together with the lipid-lowering effects and anti-atherosclerotic properties of sardilipin [18,24,73] and the prometabolic activity of animon complex, exert a positive synergistic effect on brain function accompanied by a transient improvement in mental performance, lasting for about 9-12 months Figure 2. The effect of CDP-choline, either alone or in combination with donepezil, as well as the effects of sardilipin, are APOE-dependent [3,[18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 56%
“…From studies designed to define APOE-related AD phenotypes, several conclusions can be drawn: (i) the age-at-onset is 5-10 years earlier in approximately 80% of AD cases harboring the APOE-4/4 genotype; brain atrophy and AD neuropathology is markedly increased in APOE-4/4>APOE-3/4>APOE-3/3; (xi) brain mapping activity shows a significant increase in slow wave activity in APOE-4/4 from early stages of the disease; (xii) brain hemodynamics, as reflected by reduced brain blood flow velocity and increased pulsatility and resistance indices, is significantly worse in APOE-4/4 (and in APOE-4 carriers in general, as compared with APOE-3 carriers); brain hypoperfusion and neocortical oxygenation is also more deficient in APOE-4 carriers; (xiii) lymphocyte apoptosis is markedly enhanced in APOE-4 carriers; (xiv) cognitive deterioration is faster in APOE-4/4 patients than in carriers of any other APOE genotype; (xv) in approximately 3-8% of the AD cases, the presence of some dementia-related metabolic dysfunctions accumulates more in APOE-4 carriers than in APOE-3 carriers; (xvi) some behavioral disturbances, alterations in circadian rhythm patterns, and mood disorders are slightly more frequent in APOE-4 carriers; (xvii) aortic and systemic atherosclerosis is also more frequent in APOE-4 carriers; (xviii) liver metabolism and transaminase activity also differ in APOE-4/4 with respect to other genotypes; (xix) hypertension and other cardiovascular risk factors also accumulate in APOE-4; and (xx) APOE-4/4 carriers are the poorest responders to conventional drugs. These 20 major phenotypic features clearly illustrate the biological disadvantage of APOE-4 homozygotes and the potential consequences that these patients may experience when they receive pharmacological treatment for AD and/or concomitant pathologies [1][2][3][4][5][18][19][20][21][22][23][24][25][26][27][28][29][30][77][78][79]. In our study, it is clear that APOE-4 carriers are the worst responders to conventional treatments Figures 3 and 4.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…APOE-4 may influence AD pathology by interacting with APP metabolism and Aβ accumulation, enhancing hyperphosphorylation of tau protein and neurofibrillary tangle (NFT) formation, reducing choline acetyltransferase activity, increasing oxidative processes, modifying inflammation-related neuroimmunotrophic activity and glial activation, altering lipid metabolism, lipid transport and membrane biosynthesis in sprouting and synaptic remodeling, and inducing neuronal apoptosis [1,[6][7][8]. In addition, multiple studies over the past two decades have demonstrated that APOE variants may affect the therapeutic response to anti-dementia drugs [9][10][11][12][13][14][15][16][17].…”
Section: Editorialmentioning
confidence: 99%